Technological innovation as a source of industrial competitiveness - Espinoza López, Javier Francisco (2021)
The competitive and changing environment in which industrial organizations operate, makes the technological innovation process the way to successfully adapt to these changes, being able to respond in a timely manner to new market needs and demands, introducing new products or improved products and implementing new processes, which mean changes in production methods, infrastructure, equipment or others; so that all these have a positive impact on the competitiveness of industrial organizations. Technological innovation is a primary factor, which becomes part of the set of intangible assets that organizations have, which allows them to anticipate or respond in a timely manner to the constant changes and demands of the market; this type of innovation is made up of product innovation and process innovation; innovating products includes the development of these with the consequent introduction of them into the market, while process innovation is constituted by the development and improvement of the internal production methods that an organization has. Technological innovation is approached as a way to differentiate itself from the competition, improve market share, reduce costs, improve quality, improve existing processes, reduce rework, improve product acceptance in the market, provide confidence about products and processes to customers as well as the organization’s stakeholders.